The love of my youth : a novel - Gordon, Mary, 1949- (Pantheon Books, 2011)
This work is a novel about first lovers meeting again after more than thirty years, walking the streets of Rome and reimmersing themselves in their lost past. Miranda and Adam, high school sweethearts now in their late fifties, arrive by chance at the same time in Rome, where they once spent a summer deeply in love, blissfully living together. At an awkward reunion, the two, who parted in an atmosphere of passionate betrayal in the 1960s and haven't seen each other since, are surprised to discover that they may still have something to talk about; they decide that, for these few weeks, they will take daily walks together. As they experience Rome, the pleasures of eye and palate, and the daily drama of the streets, they review their lives (married to others, and with grown children) and gradually explore not just what matters to them now, but what happened to them long ago. Miranda and Adam are masterfully portrayed characters, intent on understanding who they are in relation to who they were. Theirs is a rich and wise story of forgiveness and reckoning.